1995
DOI: 10.1038/ng0895-383
|View full text |Cite
|
Sign up to set email alerts
|

Diverse spermatogenic defects in humans caused by Y chromosome deletions encompassing a novel RNA–binding protein gene

Abstract: We have detected deletions of portions of the Y chromosome long arm in 12 of 89 men with azoospermia (no sperm in semen). No Y deletions were detected in their male relatives or in 90 other fertile males. The 12 deletions overlap, defining a region likely to contain one or more genes required for spermatogenesis (the Azoospermia Factor, AZF). Deletion of the AZF region is associated with highly variable testicular defects, ranging from complete absence of germ cells to spermatogenic arrest with occasional prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
535
1
14

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,104 publications
(568 citation statements)
references
References 41 publications
11
535
1
14
Order By: Relevance
“…Northern hybridization and RT-PCR were performed as described (1). Tissues were homogenized in Trizol according to instructions (GIBCO͞BRL, Bethesda).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Northern hybridization and RT-PCR were performed as described (1). Tissues were homogenized in Trizol according to instructions (GIBCO͞BRL, Bethesda).…”
Section: Methodsmentioning
confidence: 99%
“…This finding suggests that DAZ proteins may function with interacting proteins to regulate translation. (ii) Four of the proteins are encoded by loci shown genetically to be required for fertility in other organisms (PUM2, BOL, hQK3, and DAZL) (1,8,(17)(18)(19). (iii) Five of the proteins have been shown biochemically to interact with DAZ [BOL, DZIP1, DZIP2, hQK3 (data not shown)] and DAZL (14,20,21).…”
Section: Identification Of Daz-interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic causes of azoospermia include chromosomal abnormalities, Y chromosome microdeletions, and specific mutations or deletions of several Y chromosomal genes 2, 3. Thus, in 1995, it was demonstrated that DAZ mutations (Yq11.23) cause various forms of human male infertility that range from oligospermia to azoospermia 4, 5. In 1997, it was reported that RBMY (Yq11.223) mutations cause azoospermia via meiotic arrest5, 6 and, in 1999, it was shown that USP9Y (Yq11.2) mutations lead to azoospermia that is secondary to hypospermatogenesis 5, 7.…”
Section: Introductionmentioning
confidence: 99%
“…While many members of the hnRNP family were discovered two or more decades ago, a family member relevant to spermatogenesis was isolated more recently. This hnRNP protein-DAZAP1-was isolated on the basis of its interaction with DAZ, a germ-cell-specific RNA-binding protein encoded on the Y chromosome that is deleted in 10 per cent of infertile men with idiopathic azoospermia (Reijo et al 1995(Reijo et al , 1996Tsui et al 2000). To determine the in vivo function of DAZAP1, Hsu et al (2008) generated Dazap1-mutant mice carrying either a floxed neomycin resistant (Fn) hypomorphic allele or a null allele.…”
Section: Rna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%